2019
DOI: 10.1002/ijgo.12987
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of individually adjusted fetal growth

Abstract: Objective To construct individualized fetal growth curves estimated by ultrasound parameters adjusted for maternal and fetal characteristics. Methods Data were retrospectively assessed from serial ultrasonographic examinations of singleton pregnancies at 12–42 gestational weeks among women without maternal or fetal conditions and full‐term delivery at the University Hospital of University of São Paulo between July 1, 2014, and December 31, 2017. Measurements included biparietal diameter, head circumference, ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The difference between male- and female-specific growth parameters has been addressed in previous studies. 13 , 14 , 15 , 16 , 17 , 18 Schwärzler et al 11 showed a significant difference in HC between genders and concluded that using sex-specific nomograms may improve the prenatal assessment of fetal growth and provide valuable additional information in high-risk cases. However, the authors did not assess the clinical significance of the utilization of gender-customized curves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between male- and female-specific growth parameters has been addressed in previous studies. 13 , 14 , 15 , 16 , 17 , 18 Schwärzler et al 11 showed a significant difference in HC between genders and concluded that using sex-specific nomograms may improve the prenatal assessment of fetal growth and provide valuable additional information in high-risk cases. However, the authors did not assess the clinical significance of the utilization of gender-customized curves.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, although gender-specific curves for estimated fetal weight and fetal biometry were published, they were not incorporated into routine prenatal practice. 17 , 18 , 20 Moreover, non–gender-customized curves are usually used. This might be partly because the clinical significance of applying gender-specific curves was not assessed.…”
Section: Resultsmentioning
confidence: 99%